Psoriasis: Classical vs. Paradoxical. The Yin-Yang of TNF and Type I Interferon - Mylonas, Alessio; Conrad, Curdin (Frontiers in Immunology, 2018)
Chronic plaque psoriasis is a common debilitating skin disease. The identification of the pathogenic role of the TNF/IL-23/TH17 pathway has enabled the development of targeted therapies used in the clinic today. Anti-TNF agents have become a benchmark for the treatment of numerous chronic inflammatory diseases such as psoriasis. Although being highly effective in psoriasis treatment, anti-TNFs can themselves induce psoriasis-like skin lesions, a side effect called paradoxical psoriasis. In this review, we provide a comprehensive look at the different cellular and molecular players involved in classical plaque psoriasis and contrast its pathogenesis to paradoxical psoriasis, which is clinically similar but immunologically distinct. Classical psoriasis is a T-cell mediated autoimmune disease driven by TNF, characterized by T cell memory and a relapsing disease course. In contrast, paradoxical psoriasis is caused by the absence of TNF and represents an ongoing IFNα-driven innate inflammation that fails to elicit T-cell autoimmunity and lacks memory T cell-mediated relapses.